Factors associated with acute postoperative pain following breast reconstruction. (March 2017) - Kulkarni, Anita R.; Pusic, Andrea L.; Hamill, Jennifer B.; Kim, Hyungjin M.; Qi, Ji; Wilkins, Edwin G.; Roth, Randy S.
Abstract: Introduction: Postmastectomy breast reconstruction has become an increasingly important component of breast cancer treatment. Unfortunately, some patients experience severe postoperative pain, placing them at risk for increased clinical morbidity and the development of disabling chronic pain. To identify patients at risk, we prospectively evaluated patient characteristics and medical/surgical variables associated with more severe acute post-reconstruction pain. Methods: Women (N = 2207; 1-week 82.8% response rate) undergoing breast reconstruction were assessed for pain experience, anxiety, depression, and sociodemographic characteristics before surgery. Pain assessments were made preoperatively and postoperatively at 1 week using validated survey instruments including the McGill Pain Questionnaire-Short Form (MPQ-SF), Numerical Pain Rating Scale (NPRS), and BREAST-Q Chest and Upper Body scale. Depressive symptoms and anxiety severity were assessed by the Patient Health Questionnaire and Generalized Anxiety Disorders Scale, respectively. Mixed-effects regression modeling was used to examine the relationships between patient characteristics and medical/surgical variables and 1-week postoperative pain. Results: Younger age; bilateral reconstruction; and severity of preoperative pain, anxiety, and depression were associated with more severe acute postoperative pain on all the pain measures and BREAST-Q. Surgical procedure type indicated less severe postoperative pain for PTRAM, DIEP, and SIEA reconstructive surgery when compared with tissue expander/implant reconstruction. Conclusions: This study identifies patients at risk for severe acute postoperative pain following breast reconstruction. These findings will allow plastic surgeons to better tailor postoperative care to improve patient comfort, reduce clinical morbidity, and enhance patient satisfaction with their surgical outcome.